2020
DOI: 10.21203/rs.3.rs-73771/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Significance between Air pollutants, Meteorological Factors and COVID-19 Infections: Probable Evidences in India

Abstract: SARS-CoV-2 (Coronavirus) disease represents the causative agent with a potentially fatal risk which is having great global human health concern. Earlier studies suggested that air pollutants and meteorological factors were considered as the risk factors for acute respiratory infection, which carries harmful pathogens and affects the immunity. The study intended to explore the correlation between air pollutants, meteorological factors and the daily reported infection cases caused by novel coronavirus in India. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 138 publications
(161 reference statements)
0
5
1
Order By: Relevance
“…Gupta et al (2020) suggested that environmental factors in semi-arid and wet regions in India were signi cantly prone to infection by COVID-19 transmission and also claimed that there is a strong signi cant positive relationship between the numbers of infections with solar radiation. Additionally, the results contradict a nding by Sahoo et al (2020) which claimed that an increase in temperature and dew points could not attenuate the transmission of COVID-19 cases surge. Furthermore, Sharma et al (2021) revealed that both temperature and air pressure reported a signi cant and negative impact on COVID-19 con rmed cases.…”
Section: Meteorological Factors and Covid-19contrasting
confidence: 97%
“…Gupta et al (2020) suggested that environmental factors in semi-arid and wet regions in India were signi cantly prone to infection by COVID-19 transmission and also claimed that there is a strong signi cant positive relationship between the numbers of infections with solar radiation. Additionally, the results contradict a nding by Sahoo et al (2020) which claimed that an increase in temperature and dew points could not attenuate the transmission of COVID-19 cases surge. Furthermore, Sharma et al (2021) revealed that both temperature and air pressure reported a signi cant and negative impact on COVID-19 con rmed cases.…”
Section: Meteorological Factors and Covid-19contrasting
confidence: 97%
“… Shahzad K et al [ 54 ] 2020 Spain 29 February to 17 July 2020 140 Pearson Spearman correlation 7 temperature, COVID-19 cases Overall empirical results show that the temperature may not be a determinant to induce COVID-19 spread in Spain, while the rising temperature may reduce the virus transmission Lasisi TT & Eluwole KK [ 55 ] 2020 Russian Federation March 21 and May 28, 2020 69 Spearman's correlation 6 Maximum temperature, minimum temperature, average temperature, rainfall findings indicated a stronger correlation between average temperature and recorded significant correlations for the other temperature variants. Sahoo MM [ 56 ] 2020 India 30th Jan 2020 to 23rd Apr 2020 85 Spearman's correlation and GAM Model 8 mean temperature, relative humidity, air pressure, rainfall, wind speed, and wind direction There are significant correlations between air pollutants and weather variables with COVID-19-infected cases Sarmadi M et al [ 57 ] 2021 UK March 21 to November 13, 2020 238 Spearman, Pearson 7 temperature, humidity, precipitation, wind speed The primary results of this study reveal that wind speed, humidity, the temperature may account for geographical variation in the spread of SARS-CoV-2 across the UK Suhaimi NF et al [ 58 ] 2020 Kuala Lumpur, Malaysia 1 January to 21 April 2020 112 Spearman correlation 5 Relative humidity, ambient temperature, wind speed, and solar radiation Spearman's correlation test showed that COVID-19 cases were positively correlated with relative humidity. Abdelhafez E et al [ 59 ] 2021 Jordan March 15 to August 31, 2020 170 Spearman, sensitivity analysis 7 Average daily temperature, relative humidity, wind speed, pressure It was found that the most effective weather parameter in the active...…”
Section: Resultsmentioning
confidence: 99%
“…A wide array of meteorological factors including particulate matter, air pollution, and heat were identified as positively associated with the spread of COVID-19. Studies identified that reported on the relationship between meteorological parameters and COVID-19 spread in different regions of the world [ [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ] are shown in Table 1 . The interplay among meteorological factors (air pollution, meteorological parameters, and climate change) ...…”
Section: Resultsmentioning
confidence: 99%
“… Significant correlations were found between air pollutants and meteorological factors with COVID cases. [ 37 ] Quetta, Karachi, Lahore, Peshawar, and Islamabad, Pakistan Daily PM 2.5 and PM 10 concentrations PM 2.5 and PM 10 samples were collected and their concentrations were measured using Beta-ray Attenuation Mass Spectrometer. The air quality data was obtained from the NASA's MODIS equipment.…”
Section: Resultsmentioning
confidence: 99%